Investigation of heavy metal concentrations for biocoke by using ICP-OES - Erdiwansyah, E.; Gani, Asri; Desvita, Hera; Mahidin, M.; Bahagia, Bahagia; Rizalman, Mamat; Mohd Rosdi, Salleh (Elsevier B.V., 2025)
The palm oil industry produces large amounts of empty oil palm bunches (EFB) waste, which can pollute the environment if it contains hazardous heavy metals. This study aims to analyze the concentration of heavy metals in EFB using the Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) method. The analysis showed that hazardous heavy metals such as arsenic (As), cadmium (Cd), mercury (Hg), and lithium (Li) were not detected in EFB samples. Calcium (Ca) was recorded as the metal with the highest concentration of 52.636,42 µg/g, followed by sodium (Na) at 863,67 µg/g and copper (Cu) at 6.12 µg/g. Variations in soaking temperature and water flow rate in the EFB preparation process affected the concentration of certain metals, such as a significant increase in Ca with increasing flow rate. These results indicate that EFB is relatively safe to use as a raw material for biocoke. It can partially replace coal as an alternative fuel in the combustion process because its calorific value is close to coal. In addition to supporting emission reduction efforts, this study provides a scientific basis for a more environmentally friendly and sustainable palm oil industry waste management strategy and opportunities for developing alternative fuels from biomass that can help improve energy efficiency in various industrial applications.